Anger mediates the effect of ostracism on risk-taking. Issue 5 (27th May 2016) - Svetieva, Elena; Zadro, Lisa; Denson, Thomas F.; Dale, Emily; O'Moore, Kathleen; Zheng, Wu Yi
Abstract : The present research tested the effects of being ostracized on risk-taking behavior and how emotional responses to ostracism mediate these effects. In two experiments, undergraduates were either ostracized or included during an Internet ball-toss game ( Cyberball ). In Experiment 1 ( N  = 52), ostracism increased self-reported risk-taking inclinations, and the relation between ostracism and risk-taking was mediated by feelings of anger, but not control. In Experiment 2 ( N  = 72), ostracism increased risky driving during a driving video game. The effect of ostracism on risk-taking was again mediated by post-ostracism anger (but not control or ostracism-induced sadness). This research suggests that anger elicited by ostracism may increase risk-taking.